2010
DOI: 10.1002/poc.1651
|View full text |Cite
|
Sign up to set email alerts
|

Triplet diphenylcarbene protected by iodine and bromine groups

Abstract: Diphenyldiazomethane having two iodine and two bromine groups at the ortho positions, (2,6‐dibromo‐4‐tert‐butylphenyl)(2,6‐diiodo‐4‐tert‐butylphenyl)diazomethane (1a‐N2), has been synthesized. Triplet diphenylcarbene 31a is generated from the precursor and is characterized by UV–Vis spectroscopy at low temperature and laser flash photolysis (LFP) techniques at room temperature. Irradiation of 1a‐N2 in a 2‐methyltetrahydrofuran (2‐MTHF) matrix at 77 K gives the UV–Vis spectrum of 31a, but ESR signals that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 61 publications
(98 reference statements)
4
19
0
Order By: Relevance
“…The different tendencies observed for zfs and T d can be explained in terms of the steric effect of the ‘wings’. We have reported that the triplet diphenylcarbenes decay in 2‐MTHF at low temperature by abstracting a hydrogen from the solvent to form the corresponding diphenylmethyl radicals . Thus, large ‘wings’ would retard the approach of 2‐MTHF to the carbene center, resulting in the high T d s.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The different tendencies observed for zfs and T d can be explained in terms of the steric effect of the ‘wings’. We have reported that the triplet diphenylcarbenes decay in 2‐MTHF at low temperature by abstracting a hydrogen from the solvent to form the corresponding diphenylmethyl radicals . Thus, large ‘wings’ would retard the approach of 2‐MTHF to the carbene center, resulting in the high T d s.…”
Section: Resultsmentioning
confidence: 99%
“…The strategy, however, encounters a limitation when bulky substituents are employed as protecting groups. Persistent triplet diphenylcarbenes are generated by photolysis of the nitrogen precursors, diphenyldiazomethanes, which are almost always synthesized from the corresponding benzhydrols via the carbamate pathway . However, synthesis of a carbamate derivative having substituents bulkier than a trifluoromethyl group at the ortho position was not successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to theoretical calculations [17,18], the length of the C-I bond (210 pm) of iodobenzene is greater than that of the C-Br bond (189 pm) in bromobenzene. Recently, we generated and characterized a triplet diphenylcarbene bearing two iodine and two bromine groups at the ortho positions, (2,6-dibromo-4- tert -butylphenyl)(4- tert -butyl-2,6-diiodophenyl)carbene 3 1b [19] (Scheme 1). This species was found to be a persistent triplet carbene, but contrary to our expectations, its half-life ( t 1/2 = 24 s) was only 1.5 times longer than that of 3 1c .…”
Section: Introductionmentioning
confidence: 99%
“…Although stabilization of singlet carbenes is now well accomplished,9 effective means for the stabilization of triplet carbenes yet remain to be put to test. A common concept is the design of sterically crowded arylcarbenes, e.g., 2,6‐dibromo‐4‐ tert ‐butyl‐2′,6′‐bis(trifluoromethyl)‐4′‐isopropyldiphenylcarbene ( v ) 10–14. This particular approach goes along with considerate spin delocalization across the molecule, thus altering the distinctive reactivity pattern and electronic configuration of a triplet carbene.…”
Section: Introductionmentioning
confidence: 99%